CHASE-Containing Histidine Kinase Receptors in Apple Tree: From a Common Receptor Structure to Divergent Cytokinin Binding Properties and Specific Functions - Daudu, Dimitri; Allion, Elsa; Liesecke, Franziska; Papon, Nicolas; Courdavault, Vincent; Dugé de Bernonville, Thomas; Mélin, Céline; Oudin, Audrey; Clastre, Marc; Lanoue, Arnaud; Courtois, Martine; Pichon, Olivier; et al. (Frontiers in Plant Science, 2017)
Cytokinin signaling is a key regulatory pathway of many aspects in plant development and environmental stresses. Herein, we initiated the identification and functional characterization of the five CHASE-containing Histidine Kinases (CHK) in the economically important Malus domestica species. These cytokinin receptors named MdCHK2, MdCHK3a/MdCHK3b and MdCHK4a/MdCHK4b by homology with Arabidopsis AHK clearly displayed three distinct profiles. The three groups exhibited architectural variations, especially in the N-terminal part including the cytokinin sensing domain. Using a yeast complementation assay, we showed that MdCHK2 perceives a broad spectrum of cytokinins with a substantial sensitivity whereas both MdCHK4 homologs exhibit a narrow spectrum. Both MdCHK3 homologs perceived some cytokinins but surprisingly they exhibited a basal constitutive activity. Interaction studies revealed that MdCHK2, MdCHK4a and MdCHK4b homodimerized whereas MdCHK3a and MdCHK3b did not. Finally, qPCR analysis and bioinformatics approach pointed out contrasted expression patterns among the three MdCHK groups as well as distinct sets of co-expressed genes. Our study characterized for the first time the five cytokinin receptors in apple tree and provided a framework for their further functional studies.